A constant phase impedance sensor for measuring conducting liquid level. (September 2021) - Rahman, Mohammad Zia Ur; Aldossary, Omar M.; Islam, Tarikul
Abstract: In the contact type capacitive liquid level sensors, when an electrode with the insulating film is immersed in polar/ionic medium, it shows constant phase behavior at metal–insulator interface due to the formation of the double layer. This double layer effect is frequently modeled by a pure capacitor but its capacitance value depends on signal frequency. Therefore, when such a sensor is excited by sinusoidal ac, the conducting liquid level measurement suffers from the error due to the fluctuation of input signal frequency. This is because the excitation frequency applied from the source meter may fluctuate. This important issue is rarely discussed for the capacitive level sensors. In addition, the design and realization of the capacitive level sensor require special arrangements for the minimization of parasitic earth capacitance, offset capacitance, and the capacitances due to leads and contact electrodes. In this paper, we propose a novel constant phase impedance sensor for the measurement of conducting liquid levels in the range of 0–4 cm for the first time. The phase angle of the device changes due to a change in the liquid level. Two important characteristics parameters of the sensor are the constant phase angle for a certain frequency range and the fractional order in the range of 0–1. Some important features of the sensor are significant sensitivity (2.1 ∘ /cm, probe 1) due to small change in conducting liquid, stable output due to fluctuation of input frequency, and the fabrication of the sensor is very simple and inexpensive. The device is finally interfaced to a phase detection circuit to convert the phase angle into a voltage signal. Highlights: Investigation of the constant phase impedance sensors for level measurement for the first time. Determination of the response characteristics of the sensor. Phenomena for the constant phase behavior. A phase detection circuit for interfacing the sensor. Fabrication is simple, inexpensive, sensitive and free from frequency error.